Evaluation of phytochemical, nutritional and sensory properties of high fibre bun developed by utilization of Kappaphycus alvarezii seaweed powder as a functional ingredient - Anita Sasue; Zalifah Mohd Kasim; Saiful Irwan Zubairi (Arabian Journal of Chemistry, 2023)
Kappaphycus alvarezii (Kapparezii) is red seaweed with various health benefits. While bread and bun are an excellent convenient food to deliver functional properties to consumers. The objectives of this study are to (i) determine the nutritional properties and phytochemical contents of buns added with Kapparezii seaweed powder (KSWP) (ii) identify the best three of five formulations through quantitative descriptive analysis (QDA) and (ii) evaluate the sensory attributes and overall acceptability of bun with added KSWP hedonic test. Five formulations with different proportions of KSWP inclusion namely A (0%), B (3%), C (6%), D (9%) and E (12%) were formulated. Bake loss were found to decrease (14.93–9.64%) with increased KSWP. The KSWP concentration had a significant effect (p < 0.05) on the phytochemical constituents of the bun with total phenolic content (TPC) (35.07 gallic acid equivalent (GAE), mg/100 g) and 2,2-diphenyl-1-picryl-hydrazyl (DPPH) activity (49.02%) were at maximum readings when 12% KSWP was incorporated into the flour. Increment of KSWP in bun reduced the moisture (35.57–24.59%) and protein content (12.51–9.60%) significantly (p < 0.05), because KSWP increases the water absorption and reduces the network produced by gluten. Carbohydrate (49.96–63.26%), ash (0.91–1.62%), fat (1.05–1.67%) and dietary fiber (4.51–13.63%) composition increased significantly (p < 0.05) with KSWP addition due to the presence of polyunsaturated fatty acids, macro- and micro-minerals in the KSWP. The QDA scores for all attributes revealed samples A and B were significantly different (p < 0.05) compared to C, D and E. Samples A, B and C have been identified as the best three formulations for further analysis using hedonic test. As for the hedonic test, significant difference (p < 0.05) was observed only for the attribute of seaweed odour. Sample C was highly accepted by the panellists. The addition of KSWP at a lower concentration has met the expectation of the consumers by altering the sensory properties, quality characteristics and nutritional properties of the bun.